WATER UPTAKE, MOISTURE ABSORPTION AND WETTABILITY OF BEECH VENEER TREATED WITH N-METHYLOL MELAMINE COMPOUNDS AND ALKYL KETENE DIMER - Hien Mai, Trinh; Minh Hung, Nguyen (Journal of Forestry Science and Technology, 2017)
With Beech veneers being treated with 10% solid content of the chemicals from paper (Alkyl ketene dimer, AKD), wood (N-methylol melamine, NMM-1) and textile industry (fatty acid modified N-methylol melamine, mNMM-2), the results showed that the treatments with these chemicals considerably increased the water repellence effectiveness (WRE) of veneers in the initial submersion phases; Then, WREs reduced significantly from 4 h of immersion to water saturation state (full-water). Moreover, with the WREs at water saturation state ranged from AKD (5.0%) to mNMM-2 (19.3%), there must be some certain chemical deposited in the cell lumen and cell wall of the treated veneers. The water repellence of the treated veneers was stable after the wetting-drying cycles. The chemicals NMM-1 and mNMM-2 that could react with hydroxyl groups or deposit into the cell wall, may induce the reduction in equilibrium moisture content (EMCR) and radial swelling (RS) for the treated veneers, while large AKD particles could not penetrate and modify the cell wall therefore did not reduce EMCR and RS in humid environment for the treated veneers. Wettability of veneers treated with AKD, NMM-1 and mNMM-2 was much lower than the untreated and control veneers.